Aplikasi Pembelajaran Interaktif Bahasa Arab Dasar untuk Anak Berbasis Android - Giatika Chrisnawati; Firman Prasetyo Nugroho (Departement of Mathematics Education, 2023)
In the development of this modern era, there have been many technologies that are growing rapidly. As for computers, which are equipment created to facilitate human work when achieving progress both in the manufacture of hardware and software and not only computers, now developments in the field of mobile phones are included in the scope of SmartPhones, which It has been developed a lot starting from features or in the field of hardware and software, there have been many mobile-based applications that have been created and have been used by the wider community today and even become an obligation for all people to use smartphones that are equipped with various features and applications in it. starting from the field of Sales, Learning, business, Health and Education and this time the author will try to make a final project in the field of basic learning aimed at children to start an early learning stage of basic introduction and basic understanding of it's a lesson, the target we will take is learning a foreign language, namely Arabic with the system that we will make is aimed at children to make it easier for them to learn Arabic, easily, clearly and certainly fun